Subchondral fracture of the femoral head in children: Differential diagnosis of pediatric hip pain. (7th July 2020) - Yamaguchi, Ryosuke; Nakamura, Tomoyuki; Yamamoto, Takuaki; Takamura, Kazuyuki; Yanagida, Haruhisa; Yamaguchi, Toru; Nakashima, Yasuharu
This report describes clinical and radiographic characteristics of two pediatric patients with a presumptive diagnosis of subchondral fracture of the femoral head made based on their clinical course and imaging findings. An 8-year-old boy and an 8-year-old girl had subchondral fracture in the femoral head without osteonecrosis, which was verified by contrast-enhanced magnetic resonance imaging. Although complete disappearance of the fracture line was confirmed in the boy, the girl had a residual femoral head deformity after conservative treatment. Subchondral fracture of the femoral head should be included in the differential diagnosis of pediatric hip pain.